2018
DOI: 10.2337/dc18-0699
|View full text |Cite|
|
Sign up to set email alerts
|

Urine Complement Proteins and the Risk of Kidney Disease Progression and Mortality in Type 2 Diabetes

Abstract: In a largely Mexican American cohort with type 2 diabetes and proteinuric DKD, urine abundance of several complement and complement regulatory proteins was strongly associated with progression to ESRD and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
(34 reference statements)
1
19
0
Order By: Relevance
“…91 In addition, the analysis of urine samples of patients with diabetes has shown the excessive secretion of complement activation factors such as factor H-related protein 2, C3a, C5a, and C5b-9 that were positively correlated to the disease progression and increased mortality rate. 93,94 Overall, these studies confirm the involvement of the complement system in DKD.…”
Section: Activation Of the Complement Systemsupporting
confidence: 72%
“…91 In addition, the analysis of urine samples of patients with diabetes has shown the excessive secretion of complement activation factors such as factor H-related protein 2, C3a, C5a, and C5b-9 that were positively correlated to the disease progression and increased mortality rate. 93,94 Overall, these studies confirm the involvement of the complement system in DKD.…”
Section: Activation Of the Complement Systemsupporting
confidence: 72%
“…Immunohistochemical staining confirmed increased staining of C7 in early DN kidneys compared with nondiabetic controls 35 . Furthermore, urinary concentrations of C3, C7, and C5b-9 correlate significantly with urinary protein excretion and eGFR in patients with diabetes 36 , 37 . However, it is less likely that nonspecific trapping of complement components in solidified glomeruli associated with DN occurs, because solidified glomeruli in FSGS do not show significant complement deposition, as in the present study.…”
Section: Discussionmentioning
confidence: 87%
“…CD59 is a transmembrane protein that inhibits formation of the membrane attack complex (MAC), thereby protecting cells from complement-mediated injury. Vaisar et al reported that lower urinary CD59 was an independent predictor of higher risk of future ESRD and allcause mortality in a Mexican-American cohort with T2DM and CKD [32]. Transgenic mice expressing human DAF and CD59 had reduced C3 and C9 deposition in the kidney and inhibition of terminal complement pathway [42], suggesting that targeting DAF and CD59 may prevent renal injury.…”
Section: Discussionmentioning
confidence: 99%